Amorphous TiO2 nanotube-derived synthesis of highly ordered anatase TiO2 nanorod arrays. (February 2016) - Zhao, Cong; Zhu, Dachuan; Cao, Shixiu
Abstract: A facile method by combining anodic oxidation and hydrothermal method was developed to construct highly ordered anatase TiO2 nanorods (TNRs) and nanotubes (TNTs). In this method, the anodic oxidation was used for preparing highly ordered amorphous TNTs, which subsequently served as highly ordered template for next reaction process. Upon hydrothermal treatment, the as-anodized amorphous template got converted to highly ordered anatase TNTs (blank sample) in without cobalt nitrate solution and TNRs (doped sample) in cobalt nitrate solution, respectively. To our best knowledge, this is first successful attempt to prepare highly ordered anatase TNRs based on the above amorphous template. The scanning electron microscope (SEM) and transmission electron microscope (TEM) observations indicate that the as-prepared anatase TNRs are composed by a large number of anatase TiO2 nanoparticles (TNPs) and the morphology at top of TNRs is different from that of its trunk. Details of the morphology, phase transformation, and growth mechanism of the obtained TNRs are discussed. In addition, the role of Co 2+ in the crystallization process had been also discussed. Graphical abstract: Highlights: The amorphous TNTs got converted to highly ordered anatase TNTs via hydrothermal method in DI water. The amorphous TNTs got converted to highly ordered anatase TNRs via hydrothermal method in cobalt nitrate solution. The visible light harvesting ability of TNRs has been enhanced via doping cobalt ions.